Cost Analysis of Telepharmacy Programs for Diabetes Mellitus Patients at Pharmacy - Nagrini, Indwi Sekar; Setiawan, Didik; Prasuma, Galar Sigit; Baig, Muhammad Ahsan Iftikhar (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2023)
Diabetes mellitus is silent killer with an increasing prevalence every year. This study aims to analyze the cost of telepharmacy services among patients with diabetes mellitus at the pharmacy using the ABC method of observational research calculated based on the activities carried out and BEP to determine the advantages and disadvantages of the pharmacy. The calculation results using the activity-based costing (ABC) method, the average cost for telepharmacy service costs was Rp. 12,612.- and the average cost incurred to run a telepharmacy services program were Rp. 124,574.- After being analyzed the pharmacy that have provided telepharmacy services, most of them still experience losses, this is because pharmacy have not been able to cover all operational costs.